Delayed replantation of avulsed permanent maxillary central incisor - with unfavorable outcome after 12 months - Anupam Saha; SV SG Nirmala; P Sahiti; N Tharay (Wolters Kluwer Medknow Publications, 2017)
Avulsion of permanent teeth constitutes a dental emergency and accounts for 1%-16% of all traumatic dental injuries. It occurs frequently among 7-14 years age group, whereas maxillary central incisors are the most commonly effected. Esthetics and occlusion function can be restored with replantation of an avulsed tooth. The purpose of this article is to describe a management of an 11-year-old male child with avulsed permanent maxillary central incisor which was replanted subsequently 48 h after root surface treatment with triple antibiotic paste. Follow-up visits showed signs of "replacement resorption."